(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The present study deals with the investigation of the ethyl acetate extracts of Avicennia officinalis leaves was assessed for an effect on the central nervous system (CNS) using neuropharmacological experimental models (muscle co‐ordination and locomotor activity) in mice. The extract used for a dose‐dependent reduction of the onset and duration of a reduction in locomotor activity. The result of ethyl acetate extract of Avicennia officinalis leaves (250, 500 and 1000 mg/kg, p.o.) mostly decreases the activity. These results suggest that the ethyl acetate extracts of Avicennia officinalis leaves possess a wide range of CNS activities, which need further investigation. These results suggest that the extract possesses CNS depressant activity.